BRCA1, BRCA2, and TP53 germline and somatic variants and clinicopathological characteristics of Brazilian patients with epithelial ovarian cancer - Caroline Stahnke Richau; Nicole de Miranda Scherer; Bruna Palma Matta; Elvismary Molina deArmas; Fábio Carvalho deBarros Moreira; Anke Bergmann; Claudia Bessa Pereira Chaves; Mariana Boroni; Anna Claudia Evangelista dosSantos; Miguel Angelo Martins Moreira (Cancer Medicine, 2024)
Abstract Background Approximately 3/4 of ovarian cancers are diagnosed in advanced stages, with the high‐grade epithelial ovarian carcinoma (EOC) accounting for 90% of the cases. EOC present high genomic instability and somatic loss‐of‐function variants in genes associated with homologous recombination mutational repair pathway (HR), such as BRCA1 and BRCA2, and in TP53. The identification of germline variants in HR genes in EOC is relevant for treatment of platinum resistant tumors and relapsed tumors with therapies based in synthetic lethality such as PARP inhibitors. Patients with somatic variants in HR genes may also benefit from these therapies. In this work was analyzed the frequency of somatic variants in BRCA1, BRCA2, and TP53 in an EOC cohort of Brazilian patients, estimating the proportion of variants in tumoral tissue and their association with progression‐free survival and overall survival. Methods The study was conducted with paired blood/tumor samples from 56 patients. Germline and tumoral sequences of BRCA1, BRCA2, and TP53 were obtained by massive parallel sequencing. The HaplotypeCaller method was used for calling germline variants, and somatic variants were called with Mutect2. Results A total of 26 germline variants were found, and seven patients presented germline pathogenic or likely pathogenic variants in BRCA1 or BRCA2. The analysis of tumoral tissue identified 52 somatic variants in 41 patients, being 43 somatic variants affecting or likely affecting protein functionality. Survival analyses showed that tumor staging was associated with overall survival (OS), while the presence of somatic mutation in TP53 was not associated with OS or progression‐free survival. Conclusion Frequency of pathogenic or likely pathogenic germline variants in BRCA1 and BRCA2 (12.5%) was lower in comparison with other studies. TP53 was the most altered gene in tumors, with 62.5% presenting likely non‐functional or non‐functional somatic variants, while eight 14.2% presented likely non‐functional or non‐functional somatic variants in BRCA1 or BRCA2.